Determinants Of Logistics Information Technology (Lit) Innovation Implementation Towards Firm Performance By Logistics Service Providers (Lsps) In Malaysia - Mat Salim, Hanisah (2023)
This study aims to identify the determinants of Logistics Information Technology (LIT) innovation implementation towards Firm Performance (FP) by Logistics Service Providers (LSPs) in Malaysia. However, many LSPs in Malaysia have not realized the need to employ technology in their operations and haven’t implemented IT and aligned their strategies with the changes in technology. Technology has been used as a competitive tool to give a competitive edge against competition and, in most instances, redesigning the sales process. With these developments, efficiency in service delivery has been the key in pushing many organizations towards implementing computer systems. LIT innovation implementation has vast potential as various logistics systems could be implemented towards improving the service delivery of modern LSPs. This research is guided by the TOE Model in identifying factors determining LIT innovation implementation by LSPs in Malaysia. PLS-SEM was used to analyzed the relationship of each construct using structural equation modelling. This research concludes a need for LSPs to further understand the importance of LIT innovation implementation and how it can shape their operations towards improving service delivery.